Biosynthesis of TiO2 nanoparticles by using natural extract of Citrus sinensis. (2021) - Fall, Adama; Ngom, Ibrahima; Bakayoko, Moussa; Sylla, Ndeye Fatou; Elsayed Ahmed Mohamed, Hamza; Jadvi, K.; Kaviyarasu, K.; Ngom, B.D.
Abstract: In this work, we report the synthesis and investigation the optical properties of titanium dioxide nanoparticles (TiO2 NPs) using natural extract orange skin natural. The Structural and optical properties of the prepared nanoparticles are characterized using several spectroscopic and microscopic methods including X-ray diffraction (XRD), Raman spectroscopy, ultraviolet–visible spectroscopy (UV–Vis), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), Photoluminescence, and high-resolution transmission electron microscopy (HRTEM). The TiO2 NPs crystalline phase structures has been confirmed by XRD and ART-FTIR. The influence of the annealing temperature of the synthesized TiO2 NPs has been observing with the photoluminescence emission at 900 °C around at 500 nm, and showing an intense increase of the emission. The formation of a dense agglomeration of particles and a mixture of diverse sizes and shapes composition of particles were confirmed respectively by HR-SEM and HR-TEM. The diameters of the nanoparticles obtained from SEM with the different calcination temperatures ranging from 700 to 900 °C are respectively 57.22 nm, 97.77 nm, 393 nm, as those obtained with TEM are respectively 31.6 nm, 88.54 nm, 96.99 nm.